Perspektif Filsafat Pendidikan terhadap Kreativitas dan Berpikir Kritis (Profil Pelajar Pancasila) dalam Meningkatkan Minat Berwirausaha di SMK: Educational Philosophy Perspective on Creativity and Critical Thinking (Pancasila Student Profile) in Increasing Entrepreneurial Interest in Vocational Schools - Virnayanthi, Ni Putu Erna Surim; Candiasa, I Made; Ratnaya, I Gede; Widiartini, Ni Ketut (Undiksha, 2024)
The main purpose of entrepreneurship learning in vocational schools is to provide students with opportunities to live independently and work to generate income. Entrepreneurship education fosters the development of learners' creativity, critical thinking, communication, and collaboration. However, although entrepreneurship has long been taught in schools, there is still debate about its effectiveness. Entrepreneurship programs in vocational schools have not been able to educate students to have the desired entrepreneurial attitudes, personalities, and abilities, thus hindering vocational school graduates from meeting community needs or becoming entrepreneurs. This study aims to provide a comprehensive understanding of the importance of educational philosophy influencing students' entrepreneurial interest in supporting entrepreneurship education. The research method used is a literature review to analyze and synthesize literature to increase student interest in entrepreneurship at SMK. The role of lecturers in providing learning and motivation is very important. In addition, empirical interest in entrepreneurship can be increased by developing a learning model with a constructivist and critical approach, and this approach can help increase awareness and entrepreneurial spirit among college graduates so that, in the end, it will give birth to a new generation of entrepreneurs who are more enthusiastic and potential.